PENGARUH STRATEGI PEMBELAJARAN AKTIF TIPE GIVING QUESTION AND GETTING ANSWER (GQGA) TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELAS VUPTD SDN 95 BARRU - Jabal Rahmat; Ummu Khaltsum; Andi Adam (Nusantara Hasana Berdikari, 2022)
The main problem in this research is How the Effect of Active Learning Strategy Type Giving Questions and Getting Answer on Learning Outcomes of Indonesian Language Class V UPTD SDN 95 Barru, This study aims to describe the Effect of Active Learning Strategy Type Giving Question and Getting Answer (GQGA) on Learning outcomes of Indonesian students in class V UPTD SDN 95 Barru. This study aims to determine the effect of the Active Learning Strategy Type Giving Questions and Getting Answers (GQGA) on Indonesian Language Learning Outcomes for Fifth Grade Students of UPTD SDN 95 Barru. The type of research used by researchers is experimental, which means research is used to find the effect of certain treatments on others under controlled conditions. The population and sample of this study were all students of class V UPTD DDN 95, totaling 9 people, and the sample being all students of class V UPTD SDN 95 Barru, amounting to 9 people. Data were collected using observation and tests, the data collected were analyzed using pretest and posttest. The results showed that the lowest value of the pretest concept assignment was 56 and the highest was 81, while in the posttest concept assignment the lowest score was 75 and the highest value was 94. The average value (mean) of the pretest was 68.36 while the posttest was 81.27. This shows that before the use of the active learning strategy of the Giving Question and Getting Answer (GQGA) type in learning, student learning outcomes were still below the KKM. However, after the implementation of the Giving Question and Getting Answer (GQGA) active learning strategy, student learning outcomes increased with the score obtained by students having reached the predetermined KKM of 70. So it can be concluded that the Giving Question and Getting Answer (GQGA) Active Learning Strategy can used to improve student learning outcomes, some of the advantages are that it can activate students during the learning process, attract students' attention and facilitate student understanding.